LCL-filter design and analysis for PWM recuperating system used in DC traction power substation - Sabran N.A.; Toh C.L.; Tan C.W. (Institute of Advanced Engineering and Science, 2023)
Voltage source inverter (VSI) had been used in dc traction power substation to deliver the trains braking energy back to the utility grid. To mitigate low order harmonics components, pulse-width-modulation (PWM) technique is commonly used in VSI controlled. As a result, the ac voltage and current waveforms may contain high frequency ripples. This paper proposes to mitigate the high frequency harmonics using LCL-filter with series R-damper. This filter offers good attenuation on harmonics with smaller size compare to other passive filter topologies. Theoretical analysis and simulation verification are conducted in designing the proposed filter. System level simulation had also been carried out. Sinusoidal grid current and voltage waveforms are recorded (THD<2%). This paper also includes damping losses analysis in conjunction with resonance peak suppression in designing the R-damper. 2022, Institute of Advanced Engineering and Science. All rights reserved.